2017
DOI: 10.1371/journal.pone.0180109
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal change in acute anterior uveitis associated with human leukocyte antigen-B27

Abstract: PurposeTo evaluate choroidal changes in eyes with acute anterior uveitis associated with human leukocyte antigen (HLA)-B27MethodsIn 44 patients with first-onset, unilateral, acute-onset (<1 week) anterior uveitis for which diagnostic work-ups revealed positivity only for HLA-B27, wide-field three-dimensional volumetric raster scan using swept-source optical coherence tomography was performed for both eyes. Choroidal thickness was measured by automated segmentation and thickness mapping and compared between eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
(25 reference statements)
1
23
0
2
Order By: Relevance
“…It has previously been demonstrated that CT is affected over the course of AAU. In HLA-B27 positive patients, the values of subfoveal CT were higher in eyes with AAU at the first onset compared with FEs [4]. A B-scan of the macular region in those eyes also revealed dilated large choroidal vessels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been demonstrated that CT is affected over the course of AAU. In HLA-B27 positive patients, the values of subfoveal CT were higher in eyes with AAU at the first onset compared with FEs [4]. A B-scan of the macular region in those eyes also revealed dilated large choroidal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Development of optical coherence tomography (OCT) technology also showed subclinical involvement of the posterior retina and choroid in some cases of AAU [2, 3]. Involvement of the choroid may cause changes in choroidal thickness (CT) or correlate with lower visual acuity in those patients [3, 4]. The OCT technology provided an opportunity to improve the monitoring of uveitic patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Толщина сосудистой оболочки в период активного воспаления также превышала норму [19]. Полученные результаты согласуются с данными большинства исследований взрослых с острыми передними увеитами, у которых обнаружено увеличение толщины сосудистой оболочки в период активного воспаления [8][9][10][12][13][14], что может быть обусловлено расширением сосудов, воспалительной инфильтрацией и отеком на фоне повышения их проницаемости. Нами отмечена худшая визуализация сосудов хориоидеи в периоды обострения увеита, что, очевидно, вызвано накоплением в межсосудистых пространствах экссудата, акустическая плотность которого сопоставима с плотностью воспаленной сосудистой стенки.…”
Section: результаты и обсуждениеunclassified
“…Попытки оценить роль этого параметра при передних увеитах [7][8][9][10][11][12][13][14] дали противоречивые результаты. В ряде работ обнаружено увеличение толщины сосудистой оболочки в субфовеолярной и парафовеолярной зонах в период активности воспаления [8,10,[12][13][14], а H. Yan и соавт. [9] продемонстрировали ее уменьшение при неактивном переднем увеите.…”
unclassified